Construção da resistência à mudança organizacional na relação entre agentes - Matos, Juscely Reis (2016)
The organizational resistance to change is commonly attributed to the change recipients, the ones labelled by the agents as the sole responsible for the occurrence of this phenomenon. As counterpoint to this traditional view, aroused an approach of corporative resistance as an attribution to both agents and recipients, by their interaction along the change process. However, we do not defend here a segregation of agent-recipient, once we consider that all involved in the process are agents of resistance construction. The objective of this study was to comprehend how resistance is created in the relationships amongst the various agents in a process of organizational change. Focusing on the consolidation of two sites pertaining to a company of the automotive industrial chain; it was adopted the qualitative approach and as research strategy the case study, considering as sources discursive materials, episodic interviews, observations and documents. The results obtained through the thematic analysis, show the occurrence of resistance in the different agents involved with the change, that rises up through actions and (re)actions of these agents along the process, beyond others reactions, such as distancing and acceptance of the change. The agency is not restricted to those responsible for planning and implementing the process, but present in others involved that shows up as capable to alter the original plans, through different ways of expressions of resistance. This study aims contributing to the field of organizational changes, bringing light to an approach of resistance yet scarcely explored, and proposing that all are agents in the resistance construction. This reflection shows up also important to the managers for them to realize how their actions are intrinsically related to the resistance phenomenon, that they fiercely try to avoid during the process of change.